Measuring the Impact of Changes in Quality of Life in Elderly People After Hemodialysis in Indonesia: Quantitative Analysis of Physical, Psychological, Functional and Social Aspects - Wantonoro, Wantonoro; Suryaningsih, Endang Koni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
The increasing number of elderly people in Indonesia brings new challenges to the health sector, especially related to degenerative diseases such as chronic kidney disease (CKD). Elderly people with CKD undergoing hemodialysis face various changes in quality of life in physical, psychological, functional, and social aspects. Although hemodialysis can extend life expectancy, its impact on the quality of life of elderly patients often receives less attention. The purpose of this study was to use quantitative methodology to evaluate the effect of changes in quality of life in elderly people after hemodialysis in Indonesia. The four main dimensions of this analysis are physical, psychological, functional, and social. The method used in this study was a cross-sectional design with quantitative methods. The study sample consisted of 135 elderly patients undergoing hemodialysis at PKU Muhammadiyah Hospital, Yogyakarta. Data was collected using a structured questionnaire that measured quality of life based on four aspects. Data analysis was carried out using the regression method with the SmartPLS approach to assess each aspect's effect on patients' quality of life. The results showed that all aspects studied significantly affected the quality of life of elderly people after hemodialysis. Social aspects had the most significant influence (p = 0.004), followed by psychological (p = 0.048), functional (p = 0.038), and physical (p = 0.030) aspects. Elderly people undergoing hemodialysis experience limitations in physical activity, emotional stress, decreased body function, and social isolation that affect their overall well-being.